Re-imagining contested communities connecting Rotherham through research - Campbell, Elizabeth 1962-; Pahl, Kate 1962-; Pente, Elizabeth ca. 20./21. Jh; Rasool, Zanib (Policy Press, 2018)
Using history, artistic practice, writing, poetry, autobiography and collaborative ethnography, this book literally and figuratively re-imagines a place, presenting a 'how to' for researchers interested in community collaborative research and accessing alternative ways of knowing and voices in marginalised communities
Title from publisher's bibliographic system (viewed on 07 Apr 2022)
Keywords: Communities / Research; Community development; Research teams; Gemeindeentwicklung; Rotherham (England) / Social conditions; Rotherham; Aufsatzsammlung